ISOLATION ANTHOCYANIN FROM ROSELLE PETALS (Hibiscus sabdariffa L) AND THE EFFECT OF LIGHT ON THE STABILITY - Siti Nuryanti; Sabirin Matsjeh; Chairil Anwar; Tri Joko Raharjo (Universitas Gadjah Mada, 2012)
This study was conducted to isolate anthocyanins from roselle petals and testing the stability toward light. Isolation of anthocyanin was accomplished by extracting roselle petals using eluents with different polarity levels. Nonpolar compounds was eliminated using n-hexane, then semipolar compounds extracted with ethyl acetate and isolated anthocyanin by solvent mixtures of methanol-HCl 0.5%. Color test to determine the presence of anthocyanin was performed with NH3 vapor, Pb-acetate 1% and Pb-nitrate 5%. The structure of anthocyanin in the roselle flower was determined using UV-Vis spectrophotometer, FT-IR and 1H-NMR. Anthocyanin stability test of the influence of light carried out in a room without light conditions (dark room) and light 25 Watt at 31 °C. The results showed that the roselle petals contain anthocyanin cyanidin-3-glucoside. Light has been found to affect the stability of anthocyanin cyanidin-3-glucoside.